Deposition of Immune Complexes in Gingival Tissues in the Presence of Periodontitis and Systemic Lupus Erythematosus - Pires, Julien Rodrigues; Nogueira, Maria Renata Sales; Nunes, Adauto José Ferreira; Degand, Débora Regina Fernandes; Pessoa, Larissa Costa; Damante, Carla Andreotti; Zangrando, Mariana Schutzer Ragghianti; Greghi, Sebastião Luiz Aguiar; de Rezende, Maria Lúcia Rubo; Sant'Ana, Adriana Campos Passanezi (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a complex chronic autoimmune disease characterized by tissue damage and widespread inflammation in response to environmental challenges. Deposition of immune complexes in kidneys glomeruli are associated with lupus nephritis, determining SLE diagnosis. Periodontitis is a chronic inflammatory disease characterized by clinical attachment and bone loss, caused by a microbial challenge – host response interaction. Deposition of immune complex at gingival tissues is a common finding in the course of the disease. Considering that, the primary aim of this study is to investigate the deposition of immune complexes at gingival tissues of SLE patients compared to systemically healthy ones, correlating it to periodontal and systemic parameters. Twenty-five women diagnosed with SLE (SLE+) and 25 age-matched systemically healthy (SLE -) women were included in the study. Detailed information on overall patient’s health were obtained from file records. Participants were screened for probing depth (PD), clinical attachment loss (CAL), gingival recession (REC), full-mouth bleeding score (FMBS) and plaque scores (FMPS). Bone loss was determined at panoramic X-ray images as the distance from cemento-enamel junction to alveolar crest (CEJ-AC). Gingival biopsies were obtained from the first 15 patients submitted to surgical periodontal therapy of each group, and were analyzed by optical microscopy and direct immunofluorescence to investigate the deposition of antigen-antibody complexes. Eleven (44%) patients were diagnosed with active SLE (SLE-A) and fourteen (56%) with inactive SLE (LES-I). Mean PD, CAL and FMBS were significantly lower in SLE+ than SLE- (p< 0,05; Mann Whitney). The chronic use of low doses of immunosuppressants was associated with lower prevalence of CAL > 3 mm. Immunofluorescence staining of markers of lupus nephritis and/or proteinuria was significantly increased in SLE+ compared to SLE-, even in the presence of periodontitis. These findings suggest that immunomodulatory drugs in SLE improves periodontal parameters. The greater deposition of antigen-antibody complexes in the gingival tissues of patients diagnosed with SLE may be a marker of disease activity, possibly complementing their diagnosis.